Effects of temperature and solvent on hydrothermal liquefaction of Sargassum tenerrimum algae. (October 2017) - Biswas, Bijoy; Arun Kumar, Aishwarya; Bisht, Yashasvi; Singh, Rawel; Kumar, Jitendra; Bhaskar, Thallada
Highlights: Sargassum tenerrimum algae was used for producing bio-oil. HTL was carried out in different solvents at 260–300 °C. Bio-oil yield increased with use of alcoholic solvent. Ester, a high valuable product is obtained with alcoholic solvent. Abstract: The influence of various solvents (H2 O, CH3 OH, and C2 H5 OH) on product distribution and nature of products during hydrothermal liquefaction of sargassum tenerrimum algae has been examined. Hydrothermal liquefaction was performed using H2 O (260, 280 and 300 °C) and organic solvents CH3 OH and C2 H5 OH (280 °C) for 15 min. The use of organic solvents significantly increased the yield of bio-oil. In the case of liquefaction with CH3 OH and C2 H5 OH, the bio-oil yield was 22.8 and 23.8 wt.% respectively whereas the bio-oil yield was 16.33 wt.% with H2 O. GC–MS analysis of the liquid products indicated the presence of various organic compounds including aromatics, nitrogenated and oxygenated compounds and higher selectivity amount of ester compounds were observed in the presence of alcoholic solvents. NMR and FT-IR showed that present of solvents have an effect on the decomposition of sargassum tenerrimum algae.